INFLUENCE OF THE DISPERSED PHASE UPON THE BEHAVIOR OF NYLON RUBBER BLENDS - CROSS-LINKING EFFECT - SEO, YS (HUTHIG & WEPF VERLAG, 1993)
Nylon 6 and crosslinked SBS rubber blends were prepared. Their impact strength tests demonstrated the possibility of the existence of a maximum in impact strength at a moderate degree of crosslinking level. However, its peak value was not so much eminent as that happened in tensile test or brittle polymer's impact test. This seems due to complex mechanism occurred in dispersed phase. Based on our experimental data, we believe cavitation is important in nylon toughening. Interpretation of nylon toughening mechanism by cavitation and particle deformation is suggested for the reason of low peak value. Even though delamination is also possible, tensile strength data support cavitation in the rubber particle which seems to be more plausible for toughened nylon 6.